Environmental Interpretation: Hermeneutic Analysis Of The Interpretation Of Anthropocentric Verses In Al-Qur'an - Abdul Fatah; Imam Taufiq (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The aim of this study is addressed to environmental problems from the perspective of the Qur'an. The focus of the research is the anthropocentric verses in the Qur'an. Anthropocentric verses are verses that have the meaning of humans as the center of the universe or humans as creatures that are super-being. The categorization of anthropocentric verses is compiled thematically (maudhû’î) using a contextual hermeneutic approach. The classification of anthropocentric verses as a result of this research are: 1) Humans as the most glorified creatures 2) Humans as creatures that have power in nature, and 3) Humans as caliphs on earth. Several hermeneutical analyzes of the anthropocentric verse have been obtained. Human must not be arrogant as creatures that degrees are glorified. Humans are instructed not to cause damage on the earth and must be able to do good ihsân to all creatures created by Allah SWT. The obligation of humans as caliphs on earth is to prosper the earth rather than damage the earth